2015
DOI: 10.1002/ppap.201500149
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Observations of the Ionic Species in a Double Dielectric Barrier Discharge Operating in Nitrogen

Abstract: Negative and positive ions generated in an atmospheric-pressure DBD with double dielectrics were identified and their relative intensities characterized with variation of water vapor concentration in the discharge, gas residence time, and inter-electrode spacing. The most abundant negative ions were O À , OH À , CN À , CNO À , NO À 2 , NO À 2 ðH 2 OÞ, and NO À 3 while the positive ions were dominated byIncreasing the water concentration in the discharge led to an increase in the intensity of H þ (H 2 O)n, NO À… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Molecular beam mass spectrometry enables the in situ detection of negative and positive ions from DBDs and the study of the ionic chemistry. In case of water vapor admixture or impurities cluster ions are measured [198,199].…”
Section: Methods and Techniquesmentioning
confidence: 99%
“…Molecular beam mass spectrometry enables the in situ detection of negative and positive ions from DBDs and the study of the ionic chemistry. In case of water vapor admixture or impurities cluster ions are measured [198,199].…”
Section: Methods and Techniquesmentioning
confidence: 99%
“…It perhaps indicates why there is also a plateau in Figure a,b as the amorphous regions react rapidly, leaving the outer surfaces of the lamellae to react more slowly, reducing the rate of formation of carbonyl and amide groups vastly. Although the adsorbed oxygen is likely to be rapidly used up in the initial scission process within the amorphous regions, previous work by the authors has shown that trace amounts of oxygen present in the gas from possible leaks or impurities in the gas will form reactive oxygen species, which will react with the surface of the BOPP film and provide the source of oxygen for the functional groups on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…The investigation of the gas-phase plasma is widely performed using various analytical techniques, including optical emission spectroscopy, laser induced fluorescence, infrared spectroscopy, mass spectrometry (MS), etc. [10][11][12] . At the same time, detailed investigations of the species detected in the liquid phase are still scarce.…”
Section: Introductionmentioning
confidence: 99%